Going to Pentecost. An Experimental Approach to Ethnographies of Pentecostalism - Annelin Eriksen; Blanes, Ruy Llera; MacCarthy, Michelle (2019)
Co-authored by three anthropologists with long–term expertise studying Pentecostalism in Vanuatu, Angola, and Papua New Guinea/the Trobriand Islands respectively, Going to Pentecost offers a comparative study of Pentecostalism in Africa and Melanesia, focusing on key issues as economy, urban sociality, and healing. More than an ordinary comparative book, it recognizes the changing nature of religion in the contemporary world – in particular the emergence of “non-territorial” religion (which is no longer specific to places or cultures) – and represents an experimental approach to the study of global religious movements in general and Pentecostalism in particular.